REGISTER BAHASA KOMENTATOR MOBILE LEGENDS DALAM TURNAMEN MPL SEASON 5 - Rosyidi, Ahmad Zuhri; Suparlan, Suparlan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
Register is a variety of languages ​​used based on usage, such as online game players who have certain types and functions of registers that distinguish the gamers profession from other professions. Mobile legends is an online game that is played in groups. In a Mobile Legends tournament, not only players are involved in a match but there will also be commentators who will guide and provide comments on the match. The purpose of this study is to analyze the form of the Register Language used by the Mobile Legends game commentator in the MPL season 5 tournament. This research is a qualitative descriptive study. Data collection was done by observing the data by replaying the MPL season 5 grand final video many times, then transcribing the video script based on the expressions used and matching the script directly. The data analysis carried out consisted of three processes, namely data selection, data processing, and conclusions. The results of this study found that there was a use of register language that came from a foreign language, namely English which was used by Mobile Legends commentators such as the words first blood, retreat, recall, and play off.